IMPLEMENTING SENGE’S LEARNING ORGANISATION MODEL IN ISLAMIC EDUCATIONAL INSTITUTIONS: A CASE STUDY OF PONDOK PESANTREN DARUNNAJAH - Sofwan Manaf; Busthomi Ibrohim; Muhammad Irfanudin Kurniawan; Fajar Suryono; Musthofa Musthofa; Duna Izfanna; Mastur (Program Studi Manajemen Pendidikan Islam, 2026)
This study aims to examine the implementation of Senge’s Learning Organisation model within the context of Islamic boarding school (pesantren) management, with a specific focus on Pondok Pesantren Darunnajah Jakarta. Employing a qualitative case study methodology, data were collected through in-depth interviews with key informants, including institutional leaders, senior teachers, and administrators, supplemented by participant observation and document analysis over six months. The findings reveal that Darunnajah has effectively operationalised the five subsystems of Marquardt’s learning organisation framework: learning dynamics, organisational transformation, people empowerment, knowledge management, and technology application, while preserving its core Islamic identity. The pesantren demonstrates continuous learning through formal and non-formal pedagogical approaches, systematic organisational transformation from a traditional to a modern governance structure, strategic human resource empowerment through professional development and international partnerships, knowledge management through structured information dissemination, and technology integration across all educational levels. Currently operating 23 branch campuses across Indonesia, Darunnajah exemplifies how learning organisation principles can drive sustainable institutional expansion. The study concludes that the successful synthesis of Western organisational learning theory with Islamic educational philosophy at Darunnajah provides a replicable model for pesantren modernisation. This research contributes to the literature by bridging the gap between learning organisation theory developed in corporate settings and its application in faith-based educational institutions.